The Effectiveness of Learning Aqidah Akhlak - Muhamad Zainul Umam (Jurnal Masohi, 2020)
The learning of Aqidah Akhlak is one part of learning Islamic education that is directed to prepare students to know, understand, acknowledge and practise Islamic law, which then become the basis of his life (way of life) through the activities of guidance, teaching, training and use of experience. Islamic religion is a Universal religion that teaches mankind about various aspects of life, both the world and Ukhrowi. The first in Islam is to oblige to Muslims to perform an education preceded by the name of the Lord. Because according to Islamic teachings, education is a necessity of human life that is absolutely to be fulfilled, in order to achieve the welfare of the life of the Hereafter. With that education, man will get various kinds of science to prepare his life, and because it begins with the name of his lord then the faith becomes strong. Keywords : Effectiveness, Learning, Aqidah Akhlak